Characterization of sacha inchi (Plukenetia volubilis) and taro (Colocasia esculenta) flours with potential application in the preparation of both gluten-free and high protein foods. [version 3; peer review: 1 approved, 2 approved with reservations, 2 not approved] - Jesús Eduardo Bravo Gómez; Ruby Aracely Narváez Cadena; Angie Paola Salas Zambrano; Karen Sofia Muñoz Pabon; Diego Fernando Roa-Acosta (F1000Research)
Background Interest in alternative sources of tubers and legumes has increased in recent years because of the constant search for raw materials that provide bioactive compounds with antioxidant potential benefits for consumers. The functionality of new raw materials is sought through physical and/or chemical modifications to develop and innovate new foods. The objective of this study was to characterize taro (TF) (Colocasia esculenta) and sacha inchi (Plukenetia volubilis) flours, obtained by the wet (SIF-WM) and defatted method (SIF-DM), as an alternative for the formulation of new functional foods. Methods The free polyphenols of the different mixtures were analyzed, and the antioxidant properties of the extracts obtained were measured using ABTS.* (2,2′-Azino-bis(3-ethylbenzthiazoline-6-sulfonic acid). The ABTS radical method, which reacts with the phenolic compounds of the food matrix, using Trolox as a standard. The blends were subjected to pasting analysis, flow profile tests, determination of viscoelastic properties (temperature sweep). Characterization of common microorganisms in these foods was performed. Results The highest protein value was obtained in the sacha inchi flour obtained by the defatted method (72.62%). The majority of components in taro were carbohydrates (85.4%). About antioxidant and determination of free polyphenols, taro flour obtained values of 2.71 μmol ET/g and 7.47 mg EAG/g, higher than sacha inchi flours. In the rheological analysis (pasting properties, flow profile, and viscoelasticity), we observed that adding taro flour in different mixtures increases the viscosity peak and a lower breakdown, while there was an increase in setback. Except for defatted sacha flour, the others presented a flow index >1 before heating, showing a dilatant fluid behavior. The presence of taro flour improves gel formation and stability. Staphylococcus aureus and Salmonella were present in the taro flour. Conclusions The flours analyzed represent a raw material with great potential for the development of products such as protein snacks due to the contribution of sacha inchi, with good expansion due to taro starch, and naturally gluten-free for people with celiac disease.